Covariant differential calculi on quantum symplectic superspace SPq1| 2 - Celik, Salih (AMER INST PHYSICS, 2017)
A unitary orthosymplectic quantum supergroup is introduced. Two covariant differential calculi on the quantum superspace SPq1|2 are presented. The h-deformed symplectic superspaces via a contraction of the q-deformed symplectic superspaces are obtained. A new h-deformation of the Heisenberg superalgebra is given. Published by AIP Publishing.
Keywords: SUPERCONFORMAL ALGEBRA; DEFORMATION; MATRIX; Physics